Canadian dentists' views on the first dental visit for children - Alai-Towfigh, Hamideh; Schroth, Robert J.; Hu, Ralph; Lee, Victor H. K.; Olatosi, Olubukola (Frontiers in Oral Health, 2022)
Introduction: Early dental visits set children on an upward trajectory, towards a lifetime of optimal oral health. The purpose of this study was to analyze data from a survey of Canadian dentists to determine their knowledge, attitudes, and behaviors regarding first dental visits. Methods: The Canadian Dental Association (CDA) surveyed general and pediatric dentists regarding the timing of the first dental visit. Demographic and practice information was collected. Analyses included descriptive analyses, bivariate analyses, and multiple logistic regression with forward stepwise selection. Significance was set at p ≤ 0.05. Results: Overall, 3,232 dentists participated. The majority were male (58.5%), general dentists (96.6%), in non-metropolitan areas (50.5%), and practiced for 20.6 ± 12.8 years. The mean age recommended for first visits was 20.4 ± 10.8 months. Only 45.4% of dentists recommended a first visit ≤ 12 months. A majority (59.5%) knew that the correct age recommended for first visits was no later than 12 months. Most dentists who had seen a patient ≤ 12 months before did not typically do so (82.3%). General dentists were 61% less likely to recommend first visits by 12 months (OR = 0.39; 95% CI: 0.16, 0.91). Dentists in Central Canada (OR = 1.83; 95% CI: 1.44, 2.32); dentists who typically saw patients ≤ 12 months (OR = 3.41; 95% CI: 2.41, 4.83); those who echoed the importance of visits by 12 months (OR = 19.3; 95% CI: 8.2, 45.71); dentists with staff that encouraged infant/toddler care (OR = 1.76; 95% CI: 1.34, 2.31); and those who knew official North American recommendations for first visits (OR = 5.28; 95% CI: 4.13, 6.76) were all more likely to recommend first visits by 12 months. Conclusions: A majority of Canadian dentists did not recommend first visits by 12 months of age, despite it being the CDA’s official position. Provider characteristics can influence the age that is recommended for first visits. Findings from this study may inform educational campaigns on early childhood oral health targeted towards dentists.